Un portrait de la santé psychologique des enseignants du collégial durant la pandémie de COVID-19 - Carla Barroso da Costa; Nathalie Loye; Karina Lapointe; Élisabeth Doyon (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In the unique context of the COVID-19 pandemic for teachers, it is essential to address their psychological health because of all the upheaval they experienced. The research discussed in this article aims to understand the affective and emotional feelings that make up the psychological health of college teachers through their teaching tasks during the pandemic. The research was conducted in the fall of 2020 in order to pursue two specific objectives : 1) to draw a portrait of teachers’ psychological health, taking into account positive manifestations of well-being and negative manifestations of psychological distress related to the work context and 2) to describe the feelings that teachers experience, taking into account their gender and their skills with technology. The research was exploratory in nature and used both quantitative and qualitative analyses to provide a detailed picture of the subject matter. A total of 148 French-speaking Quebec college teachers voluntarily responded to a self-administered online questionnaire. The quantitative results highlight the preponderance of positive versus negative feelings experienced by the teachers, as well as differences in their psychological health according to their gender and their ability with technology. The qualitative results, for their part, allow us to deepen the teachers’ reflections on certain aspects of their psychological health. Finally, the study provides avenues for action adapted to certain aspects experienced by the teachers in order to promote their psychological health.